IMPLEMENTASI JAPAN PLATFORM DALAM PENGADAAN HUMANITARIAN ASSISTANCE MELALUI HEALTH SECURITY BAGI PENGUNGSI ROHINGYA DI COX'S BAZAAR 2019-2020 - Hasna' Zahidahni Hamidah (2022)
The humanitarian crisis in Rakhine, Myanmar, forced hundreds of thousands of people to flee to Bangladesh in 2017, which hosts millions of refugees and makes Cox's Bazaar the largest refugee camp globally. Refugee conditions in Cox's Bazaar still have limited facilities needed by refugees. The concerted efforts of the various international communities are urgently needed. Japan Platform (JPF), one of Japan's coordinating institutions that focuses on refugee issues, presents a humanitarian assistance program through joint coordination with NGOs, the Japanese government, and the private sector. The health program, one of the most urgent needs of millions of Rohingya refugees, is implemented by IVY and SCJ as an NGO member of JPF, focusing on improving health facilities and reconstructing WASH facilities in refugee camps. This study aims to explain how the implementation of JPF humanitarian assistance in the realm of Health security to Rohingya refugees in Cox's Bazaar. Using descriptive qualitative research and analysis with the concept of Humanitarian Assistance and Health Security, the study results show efforts to fulfill health insurance for refugees, which are carried out through humanitarian assistance programs. However, some obstacles and challenges have not demonstrated the program's significance to the health problems of refugees.